The interaction of alpha thalassaemia and sickle cell-beta zero thalassaemia. - Vyas, P; Higgs, D; Weatherall, D; Dunn, D; Serjeant, B; Serjeant, G (1988)
The effects of alpha thalassaemia on sickle cell-beta zero thalassaemia have been studied by comparing haematological and clinical features in four subjects homozygous for alpha thalassaemia 2 (2-gene group), 27 heterozygotes (3-gene group), and 55 with a normal alpha globin gene complement (4-gene group). Alpha thalassaemia was associated with significantly higher haemoglobin levels and lower reticulocyte counts independent of the presence of splenomegaly. Contrary to expectation, alpha thalassaemia was associated with small but significant increases in mean cell volume and mean corpuscular haemoglobin concentration. Splenomegaly at age 5 years and episodes of acute splenic sequestration were significantly more frequent in the 4-gene group. There were no significant differences in painful crises, acute chest syndrome, or other clinical features.